Breast cancer diagnosis - a wale up call to increase physical activity and reduce sedentary behavior? - Amirfaiz, S.; Shahril, M.R.; Nurnazahiah, A.; Lew, W.S.; Lua, P.L. (2019)
Physical activity (PA) and sedentary behaviour (SED) are established risk factors for breast cancer (BC) occurrence and recurrence. However, it is still unknown if BC diagnosis can induce lifestyle changes in BC survivors throughout the survival period. This study was conducted to determine the difference in PA and SED behaviour among healthy women, short-term breast cancer (BC) survivors and long-term BC survivors. In this cross-sectional study, purposive sampling method with predetermined inclusion and exclusion criteria were used to recruit 31 healthy women, 32 short-term BC survivors, and 48 long-term BC survivors from two government hospitals in Terengganu and Kelantan. Short-term and long-term BC survivors were defined as those wit years, or >5 years duration since BC diagnosis, respectively. PA and SED behaviour were objectively assessed for seven consecutive days using ActivPAL accelerometers and data processing was conducted using MATLAB software. Sociodemographic data and anthropometric measurements were also recorded. Difference between groups was analysed using one-way ANCOVA with age as covariate. The result of this study showed that healthy women had significantly lower number of SED sporadic bouts (<10 mins), lower number of SED breaks, shorter average SED bouts duration, lower number of lowintensity stepping, lower activity energy expenditure and shorter standing time when compared against short-term and long-term BC survivors. No significant difference was observed in all PA and SED parameters between short-term and long-term BC survivors. In conclusion, our findings suggest that a diagnosis of BC acted as a kick-start to increase PA levels and reduce SED behaviour, and the active lifestyle was maintained even after prolonged duration of BC survival. A comprehensive prospective cohort study spanning before and throughout cancer survival period is recommended to be done to ascertain this trend of PA and SED behaviour.